ҚОРАҚАЛПОҒИСТОН ТАБИИЙ ШАРОИТИДА ЖАЙРОН – GAZELLA SUBGUTTUROSA ПОПУЛЯЦИЯЛАРИНИНГ ҲОЛАТИ БЎЙИЧА ЯНГИ МАЪЛУМОТЛАР - Торемуратов, М.Ш.; Азимов, Д.А.; Жуманов, М.А.; Алламуратов, Ш.Т. (SCIENCE and SOCIETY, 2019)
It the result of the research conducted in the Karakalpak section of the Ustyurt plateau at a distance of 829 km in three directions - Itibai-Karavaur-Shakhpakhta, Shakhpakhta-Asaka-audan-Kaplankir and Kaplankir-Asaka-audan-Uru-Itibai, in total 73 species of gazella were registered , including 70 living and 3 skulls of dead gazelles. It was noted that gazelles form small groups.